Teachers' Competence as an Avenue for "Learning Through Play Pedagogy" in Preschools: A Case of Makindye Ssabagabo Division - Ngalonsa, Luciana; Ocan, Johnson; Adyanga, Akena Francis (East African Journal of Education Studies, 2024)
he purpose of this study was to establish whether teacher competence can enhance the use of learning through play (LTP) pedagogy in preschools. Specifically, the objectives of the study were to; examine how teachers' knowledge of the strand matter influences the use of learning through play in preschools, to establish whether teachers' knowledge about learners influences the implementation of learning through play in preschool, and to assess teachers' pedagogical knowledge needed on the use of learning through play in pre- schools. The study was guided by scaffolding instruction as a teaching strategy from the social constructivist theory by Levy Vygotsky (1978). The study adopted a case study design. The study population comprised preschool class teachers, heads of sections, head teachers, and pupils in class observation. Purposive sampling was used to apportion individual members selected. Data was collected using the interview schedule, focus group discussions and documentary analysis. The qualitative data was analysed using content analysis and presented in narrative form. These techniques involved observing the study participants & behaviour and drawing conclusions based on their responses and actions in the way they engaged in incorporating the learning through play pedagogy. The main findings of the results highlighted and approved that some of the teachers were competent in using the learning through play pedagogy while others still used the teacher-centred approach. Teachers conducted play without a pre-conceived pedagogical purpose. Others still involved children in the learning process in the absence of play. Further investigation revealed that those doing it well had received continuous professional development support, unlike the rest. In terms of contribution, the research recommended pedagogical advancements by showcasing the benefits of learning through play. The novelty of the study concluded that the problems addressed in this research and the suggestions presented provide the basis for improving ECD practices while using play in learning